Pengetahuan dan Sikap Petani terhadap Keberadaan Industri di Kabupaten Batang serta Dampaknya pada Praktik Keberlanjutan Pertanian - Rahmaningtyas, Avivah; Fauziah, Irma; Fadhilah, Muhammad Luthfie (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the effect of farmers’ knowledge on attitude and the effect of attitude on farming sustainability practices in Batang Regency. The research is motivated by the establishment of the Batang Special Economic Zone (SEZ) in 2025, which influences farmers’ behavior near SEZ. The research sample consisted of 200 farmers from Gringsing, Limpung, and Tulis sub-districts, which are closest to Batang SEZ This number met the minimum requirement of 170 respondents (the number of indicators multiplied by 10). Primary data were collected through interviews using questionnaire in July 2025. The study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that the Knowledge variable has a significant positive effect on Attitude (T-statistic = 11.333 > 1.960; path coefficient = 0.570). Furthermore, Attitude significantly influences Farming Sustainability (T-statistic = 4.669 > 1.960; path coefficient = 0.270).